Relationship between Neutrophil-Lymphocyte Ratio and Disease Severity in COVID-19 Patients in Isolation Ward of Dr. Soetomo General Teaching Hospital - Heri Krisnata Ginting; M. Vitanata Arfijanto; Tri Pudy Asmarawati; S. Ugroseno Yudho Bintoro (Institute of Medico-legal Publications Pvt Ltd, 2022)
This study was conducted to prove the relationship between the neutrophil-lymphocyte ratio and theseverity of COVID-19. A retrospective cohort study using medical record data of inpatients from Juneto July 2020. Analysis of the NLR relationship and the degree of severity using the Mann Whitney testif the data had an abnormal distribution. Significant if p<0.05 and 95% confidence interval. If there weresignificant results, we try to measure the cut-off of NLR value to predict severe and non-severe clinicalsymptoms. Total study subjects were 110 patients, with a male as many as 65 (59.1%), the median agewas 53.5 years (range 20-88). Most of the comorbidities were diabetes mellitus (35.5%), followed byhypertension (30%). The severity of clinical symptoms was 50% in the non-severe and severe groups,respectively. The NLR value was higher in the severe group. Mann-Whitney test showed significantdifferences in the value of NLR between the severe group and the not severe group with the p-value<0.001. Receiver operating characteristic (ROC) curve analysis area under the curve (AUC) of NLRon day-1 was 0.716 (CI 95%: 0.605 - 0.826), and the cut-off point of the prediction severity diseaseat day-7 was ≥ 6.14 with a sensitivity of 71% and a specificity of 69.1%. The neutrophil-lymphocyteratio value with severe symptoms was higher than the neutrophil ratio value for lymphocytes with nonseveresymptoms in patients with COVID-19.